2021
DOI: 10.3390/atmos12060777
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Major Impact of Planetary Boundary Layer Schemes on Simulation of Vertical Wind Structure

Abstract: The structure and evolution of the atmospheric planetary boundary layer (PBL) plays an important role in the physical and chemical processes of cloud–radiation interaction, vertical mixing and pollutant transport in the atmosphere. The PBL parameterization scheme describes the vertical transport of atmospheric momentum, heat, water vapor and other physical quantities in the boundary layer. The accuracy of wind field simulation and prediction is one of the most significant parameters in the field of atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
4
7
0
Order By: Relevance
“…This strong overestimation is a known feature of the BouLac PBL scheme used in this study and others reported similar overestimation of wind speed (e.g. Tyagi et al, 2018;Zhang et al, 2021). As dust emissions scale non-linearly with wind speed that are above a threshold (Leung et al, 2022) this raises the potential to overestimate dust emissions if winds are overestimated.…”
Section: Discussionsupporting
confidence: 72%
“…This strong overestimation is a known feature of the BouLac PBL scheme used in this study and others reported similar overestimation of wind speed (e.g. Tyagi et al, 2018;Zhang et al, 2021). As dust emissions scale non-linearly with wind speed that are above a threshold (Leung et al, 2022) this raises the potential to overestimate dust emissions if winds are overestimated.…”
Section: Discussionsupporting
confidence: 72%
“…The magnitude of the 10-m wind speed increase from 1000 LST on 18 January was larger in the four simulations than in the observations. The wind speed decrease in urban areas due to buildings was not well-represented in the numerical simulations, similar to other numerical simulations [28][29][30]. At 925 and 850 hPa, the general tendencies of the simulated air temperatures in the four simulations reproduced those in the radiosonde observation.…”
Section: Simulationssupporting
confidence: 71%
“…The microwave radiometer (HATPRO-G5, RPG, Meckenheim, Germany) is a passive microwave remote sensing device that can continuously acquire atmospheric thermal parameters such as temperature and humidity in the vertical range of 0-10 km in real time [18]. The microwave radiometer has two receivers, including seven frequency channels for water-vapor absorption lines (K-band 22.24-31.40 GHz) and seven frequency channels for oxygen absorption lines (V-band 51.26-58.00 GHz).…”
Section: Microwave Radiometermentioning
confidence: 99%